Gene Expression Correlates with Process Rates Quantified for Sulfate- and Fe(III)-Reducing Bacteria in U(VI)-Contaminated Sediments - Akob, Denise M.; Lee, Sang H.; Sheth, Mili; Küsel, Kirsten; Watson, David B.; Palumbo, Anthony V.; Kostka, Joel E.; Chin, Kuk-Jeong (Kuki) (Frontiers in Microbiology, 2012)
Though iron- and sulfate-reducing bacteria are well known for mediating uranium(VI) reduction in contaminated subsurface environments, quantifying the in situ activity of the microbial groups responsible remains a challenge. The objective of this study was to demonstrate the use of quantitative molecular tools that target mRNA transcripts of key genes related to Fe(III) and sulfate reduction pathways in order to monitor these processes during in situ U(VI) remediation in the subsurface. Expression of the Geobacteraceae-specific citrate synthase gene (gltA) and the dissimilatory (bi)sulfite reductase gene (dsrA), were correlated with the activity of iron- or sulfate-reducing microorganisms, respectively, under stimulated bioremediation conditions in microcosms of sediments sampled from the U.S. Department of Energy’s Oak Ridge Integrated Field Research Challenge (OR-IFRC) site at Oak Ridge, Tennessee. In addition, Geobacteraceae-specific gltA and dsrA transcript levels were determined in parallel with the predominant electron acceptors present in moderately and highly contaminated subsurface sediments from the OR-IFRC. Phylogenetic analysis of the cDNA generated from dsrA mRNA, sulfate-reducing bacteria-specific 16S rRNA, and gltA mRNA identified activity of specific microbial groups. Active sulfate reducers were members of the Desulfovibrio, Desulfobacterium, and Desulfotomaculum genera. Members of the subsurface Geobacter clade, closely related to uranium-reducing Geobacter uraniireducens and Geobacter daltonii, were the metabolically-active iron-reducers in biostimulated microcosms and in situ core samples. Direct correlation of transcripts and process rates demonstrated evidence of competition between the functional guilds in subsurface sediments. We further showed that active populations of Fe(III)-reducing bacteria and sulfate-reducing bacteria are present in OR-IFRC sediments and are good potential targets for in situ bioremediation.